Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let be the following sequence $x_{n}$, $n\geq0$, $0<x_{0}<1$ that satisfies the following recurrence: $$ x_{n+1}=x_{n}-x_{n}^2+x_{n}^3-x_{n}^4+x_{n}^5-x_{n}^6$$

Having given this, i'm required to calculate: $$\lim_{n\rightarrow\infty} n x_{n} $$

share|cite|improve this question

1 Answer 1

up vote 3 down vote accepted

The recurrence yields $$ \frac{x_{n+1} }{x_n} = (1-x_n) (1+x_n^2 + x_n^4) .$$

For $z\in (0,1)$ we have $ 0< (1-z)(1+z^2+z^4) < 1$ so $x_n$ is montonically decreasing and non-negative. Also note that since $x_n$ is a non-negative sequence we have $0\leq x_n \leq 1$ for all $n\in \mathbb{N}$ (for if $x_k>1$ then $x_{k+1}<0$). Thus $x_n\to x$ where $x\in[0,1].$ It must satisfy $$x=x(1-x)(1+x^2+x^4)$$ which can be written $$ x\left((1-x)(1+x^2+x^4) -1\right)=0.$$ Thus $\displaystyle \lim_{n\to \infty} x_n=0$ and consequentially, $\displaystyle \lim_{n\to\infty} \frac{x_{n+1}}{x_n} = 1.$

Now we calculate $$ \frac{(n+1) - n}{\frac{1}{x_{n+1}} - \frac{1}{x_n} }= \frac{x_{n+1} x_n}{x_n - x_{n+1}}= \frac{x_{n+1}x_n}{x_n^2-x_n^3 +x_n^4 -x_n^5 +x_n^6} $$

$$= \frac{x_{n+1}/x_n }{1-x_n +x_n^2 - x_n^3 + x_n^4}\to 1.$$

Hence, by the Stolz–Cesàro theorem we conclude $\displaystyle \lim_{n\to\infty} nx_n =1.$

share|cite|improve this answer
great solution! Thanks. – OFFSHARING Jun 2 '12 at 14:40

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.